Influenza in COVID-19 pandemic, epidemiological characteristics, approaches to vaccination - E. I. Krasnova; G. S. Karpovich; V. V. Provorova; A. E. Shestakov; Yu. V. Kazakova (Лечащий Врач)
Influenza is an acute highly contagious respiratory infection, caused mainly by influenza A, B and C viruses. Influenza is of particular importance among other infectious diseases, due to the high virulence of the pathogen, widespread distribution, and the ability to spread pandemic. However, at the present stage, serious changes are registered in the epidemic process of influenza. The leading in these processes undoubtedly belongs to the ongoing COVID-19 pandemic, as well as to other events directly related to this pandemic. This article highlights the current epidemiological characteristics of influenza infection during the COVID-19 pandemic, and considers the likely reasons for the development of such changes. Mass immunization against influenza, introduced according to WHO recommendations, has demonstrated convincing results: the use of influenza vaccines has reduced the risk of morbidity in healthy populations by 70-90%. Moreover, vaccination of the elderly reduces the number of serious illnesses and complications by 60% and deaths by 80%. This method of fighting influenza is also a priority in Russia.